The New Policing - Mclaughlin, Eugene (Sage Publications, 2007)
The New Policing provides a comprehensive introduction to the critical issues confronting policing today. It incorporates an overview of traditional approaches to the study of the police with a discussion of current perspectives. The book goes on to examine key themes, including the core purpose of contemporary policework; the reconfiguration of police culture; organizational issues and dilemmas currently confronting the police; the managerial reforms and professional innovations that have been implemented in recent years; and the future of policing, security, and crime control. In offering this discussion of the nature and role of the police, The New Policing illustrates the need to re-examine and re-think the theoretical perspectives that have constituted policing studies. Examining evidence from the UK, the USA, and other western societies, the book promotes and enables an understanding of the cultural and symbolic significance of policing in society.